2015
DOI: 10.1149/2.0041505jes
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Conductive Salt Ion Selection on EDLC Electrolyte Characteristics and Carbon-Electrolyte Interaction

Abstract: This study compares several electrolytes for application in electrochemical double layer capacitors (EDLCs), as well as their influence on double layer formation on different activated carbon materials. While propylene carbonate (PC) was used as electrolyte solvent in all cases, the applied conductive salt was varied. A change in conductive salt was found to have a great impact on solubility as well as the electrolytes' ion transport properties. Most importantly the choice of conductive salt strongly influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 52 publications
6
47
0
Order By: Relevance
“…This is very interesting because it has been shown that, on the contrary, the selection of salt has a strong influence on the operating voltage of PC‐based EDLCs . By comparing the operating voltage results with the results of the same conducting salts in PC (which have been obtained under comparable conditions), interesting dissimilarities were observed . On the one hand, Et 4 N + seems to be more stable in ACN (−1.6 V vs. Ag) than in PC (−1.3 V vs. Ag).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…This is very interesting because it has been shown that, on the contrary, the selection of salt has a strong influence on the operating voltage of PC‐based EDLCs . By comparing the operating voltage results with the results of the same conducting salts in PC (which have been obtained under comparable conditions), interesting dissimilarities were observed . On the one hand, Et 4 N + seems to be more stable in ACN (−1.6 V vs. Ag) than in PC (−1.3 V vs. Ag).…”
Section: Resultsmentioning
confidence: 93%
“…in which E is the cell voltage [V], i is the current [A], t d is the discharge time [s], m am is the active‐material weight of both electrodes [g], and dE / dt is the slope of the discharge curve [mV s −1 ] …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations